2007
DOI: 10.20529/ijme.2007.005
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric practices related to HIV in Kerala

Abstract: This survey of obstetricians' knowledge and practices in two districts in Kerala, India, finds a number of unethical practices: most providers are unaware of the value of the rapid screening test for HIV, they do not give pregnant women the option to refuse testing; testing is done without counselling, private doctors refer pregnant women who test positive to government hospitals, and some health services have separate facilities for pregnant women who test positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“… 20 23 A number of studies reported staff reluctance to use RDT/POCT, citing reasons such as distrust of their results and apprehension about the reaction of clients to a rapid test result, as well as staff not being aware of RDT/POCT availability or not having the time to attend training for them. 24 29 In summary, a lack of interest, poor investment in training, negative perceptions regarding its benefits, reluctance due to change posed in their workflow, and resultant attitudes impeded their implementation. Other barriers were high costs, preference, and mistrust in accuracy.…”
Section: Resultsmentioning
confidence: 99%
“… 20 23 A number of studies reported staff reluctance to use RDT/POCT, citing reasons such as distrust of their results and apprehension about the reaction of clients to a rapid test result, as well as staff not being aware of RDT/POCT availability or not having the time to attend training for them. 24 29 In summary, a lack of interest, poor investment in training, negative perceptions regarding its benefits, reluctance due to change posed in their workflow, and resultant attitudes impeded their implementation. Other barriers were high costs, preference, and mistrust in accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to offer systemic HIV education and increase voluntary counseling and testing (VCT) acceptance by increasing antenatal testing facilities, improving the knowledge and sensitization of health care providers (Choudhury & Kutty, 2007;Sinha et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since it may take time to cover the entire antenatal population for identification of HIVpositive pregnant mothers and initiate PMTCT for them, a simpler method needs to be evolved whereby pregnant women who are at high-risk for HIV infection can be profiled, and focused services provided for this population. Studies have assessed HIV awareness, attitudes, acceptance and barriers to perinatal testing, risk of mother to child transmission, and prevalence of abuse among pregnant women in India (Brown et al, 2001;Choudhury & Kutty, 2007;Kunte et al, 1999;Purwar, Jeyaseelan, Varhadpande, Motghare, & Pimplakute, 1999;Rahbar, Garg, Tripathi, Gupta, & Singh, 2007;A. Rogers et al, 2006;Samuel et al, 2007;Shrotri et al, 2003;Singh, Fukuda, Ingle, & Tatara, 2002) (Johnson, Dorrington, Bradshaw, du Plessis, & Makubalo, 2009;Kipp et al, 2009;Lemos, Gurgel, Rivas, & de Souza, 2009).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…For example, Richardson and Bolle [11] and Green and Platt [10] report the case of a doctor requiring that an HIV patient use a separate toilet in a hospital to control the transmission of infection. Other studies [10,[12][13][14] report that people with HIV, admitted to health institutions for treatment, are isolated, even when it involves the use of eating utensils. Such experiences discourage people with HIV from seeking care from health providers.…”
Section: Introductionmentioning
confidence: 99%